1988
DOI: 10.1002/1097-0142(19880915)62:6<1091::aid-cncr2820620611>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Exocrine pancreatic function following intraoperative irradiation of the canine pancreas

Abstract: Twenty-four beagles received intraoperative irradiation (IORT) with 6 meV electrons to the pancreas and the duodenum. Intraoperative irradiation doses of 17.5 to 40 Gy were given. Billroth I1 gastrojejunostomy was done to bypass the irradiated duodenum. Six control dogs received only the Billroth I1 surgery. Two weeks postoperatively, irradiated dogs were given 50 Gy of 6 MV X radiation (externalbeam radiation [EBRTJ) to the pancreas and duodenum in 2 Gy fractions over a 5-week period. Dogs were monitored clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 11 publications
0
34
1
Order By: Relevance
“…Similar to the duodenum, the motion of the pancreas is limited and the majority of it is within the target volume. Radiation induced damage of the pancreas predominantly decreases the endocrine and exocrine functions of the pancreas (30,31). In the present study, DA-VMAT was found to be marginally more effective than the other three technologies in D1, 5 and 10 cm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the duodenum, the motion of the pancreas is limited and the majority of it is within the target volume. Radiation induced damage of the pancreas predominantly decreases the endocrine and exocrine functions of the pancreas (30,31). In the present study, DA-VMAT was found to be marginally more effective than the other three technologies in D1, 5 and 10 cm 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows an overall summary of the recommended doses of IORT for abdominal and retroperitoneal organs in humans. When IORT doses as high as 40 Gy were delivered to the canine pancreas, pancreatic exocrine dysfunction or marked histological changes were not noted after short‐term follow‐up (≤4 months) 10,21. Corroborative data on the pathological observations in human pancreas after IORT in several clinical reports clearly show that endocrine and exocrine function is maintained in pancreatic cancer patients, whose life expectancy is typically 6–18 months.…”
Section: Iort For Pancreatic Adenocarcinomamentioning
confidence: 98%
“…Hemorrhage from the upper gastrointestinal tract has been reported,9,11,12,13 however, so irradiation of the duodenum should be minimized. The upper limit of the intraoperative radiation dose in animals is considered to be 20–30 Gy for normal duodenum14,15 and 30 Gy for normal pancreas 14…”
Section: Discussionmentioning
confidence: 99%